SOME ISSUES OF LEGAL REGULATION OF ENTREPRENEURIAL ACTIVITY OF NON-GOVERNMENTAL ORGANIZATIONS - Bekzod Narimanov (Scholar Express Journals, 2023)
In the modern world, there is a tendency to decentralize state authority and to tackle the majority of societal problems through nongovernmental organizations rather than through official institutions. In Uzbekistan, the number of non-governmental, non-profit groups has grown recently, and they have contributed to the resolution of several social issues. As the market economy evolves, it is also well recognized that entrepreneurship is growing. However, there are a number of significant concerns with regard to how NGOs might conduct their entrepreneurial operations. The difficulties surrounding the legal regulation of NGO commercial operations, current concerns, and potential remedies are discussed in this article using a scientific and legal approach
Keywords: public councils; entrepreneurial activity; branch; public fund